Evaluation of reproduction by seed of the sour pitaya (Stenocereus gummosus) in Baja California Sur, Mexico - León de la Luz, José Luis; Domínguez Cadena, Raymundo (Instituto de Ecología, A.C., 1991)
The sour pitaya (also cactus dagger, Stenocereus gummosus) is a widely distributed species along the Baja California peninsula. This species shows the following characteristic features: a) a decumbent growth, which allows vegetative dispersion; b) in spite of producing a relative high proportion of fruits with viable seeds, propagation pattern seems to be by the asexual way exclusively. The goal of this work is to contribute to the knowledge of seed reproduction potential in this species. Among other results it was found that only 30% of the floral buds become fruits. Germination requires a wash of the arillate cover and a light scarification. Seed ingestion by certain birds increases the efficiency of germination. The energy invested by each plant to flower and to the fruit production must be high, and it can be justified only if we assume that a fraction of the seeds are able to develop mature individuals and maintain the genetic diversity of the population.